A internet da natureza na gestão municipal: panorama e desenvolvimento de uma aplicação - Paula Santos, Maria Inês Corrêa de (2022)
Since the beginning of cities construction, through its growth and development processes, driven to serve human interests, urban architecture has always focused on built spaces enhancement, leaving natural landscapes aside. By following urban forests opposite paths, technologies have risen and grows even more as cities has growth, which is why this dissertation is focused on development and applied technologies at Sao Paulo state urban forests, one of Brazil's tech hubs. We started with a systematic review abut world's urban forests technologies, followed through electronic forms, to evaluate these technologies uses in Sao Paulo state cities, that ends with a current technology demonstration, widely applied worldwide, except for environmental purposes: sensors taken; in this case, Near Field Communication (NFC), as an ally in areas management and planning, thus having smart green cities. Regarding to the systematic review, three databases were researched: SciELO, Scopus and Web of Science, as thirty-one articles were found after the entire review process. It was observed that current technologies applied are mostly related to remote sensing, and most authors are Chinese and Brazilian, demonstrating our researcher’s importance. Through the electronic forms sent to the municipalities of São Paulo participating in the program Município VerdeAzul (PMVA) and to specialists in urban forests, it was observed that the teams responsible for urban forests are composed of up to three people (72%), that 81% do not use any management software because of the high cost (43%) and lack of training (19%). In relation to the most used technologies, we have the remote sensing by satellite imaging followed using drones, which was also repeated in the survey with the experts. Regarding the use of NFC, two models were installed: tag installed inside the trunk (NFC-E) and sensor encapsulated inside a plastic nail (NFC-P). It was observed that the NFC-P is more efficient than the NFC-E, due to less damage to the tree during installation and durability. Finally, the development of a functional prototype for management that is linked to the NFC technology. Through this study it was possible to notice that the most used technology in urban forests is the classic remote sensing, and the sensors (active and passive) and software are still little used but can be effective to help in the management and planning of these areas.